O mercado da segurança privada a construção de uma abordagem a partir de uma sociologia econômica - VILAR, Flávio Sérgio de Oliveira (2009)
There is in contemporary societies an increasing interest in understanding violence as well as improving measures of security in order to contain it. An effort has been made to understand the complex process of the State s dimensions specially those related to wide range public policies. The aim is to understand why socially strategic sectors, specially security, so far under State responsibility, is now being shared with the market and people even accept their tendency of being dominated by market. The phenomenon of commodification of security is not a new one but has taken place more intensely in the decade of 1970 in many countries. The subject is a complex one. The causes, consequences and meaning of commodification of security is attracting a deserved attention from scholars. The knowledge of this phenomenon must contribute to a better understanding of many aspects of its social dynamics that has great relevance from the economic, cultural and political view. This work adopts the approach of Economic Sociology, supported by the main contribution of Max Weber, Karl Marx and contemporary sociologists